Propagation Properties of Partially Coherent Flat-Topped Beam Rectangular Arrays in Plasma and Atmospheric Turbulence - Xinkai Ma; Hui Zhang; Yuanhao Zhao; LinXuan Yao; Changchun Yu; Yaru Gao; Yangsheng Yuan; Yangjian Cai; Bohan Guo (Photonics)
Propagation properties represent a critical aspect of laser beams utilized in free space optical (FSO) communications. We examined the evolution characteristics of the electric field associated with partially coherent flat-topped beam rectangular arrays propagating bidirectionally through the turbulent atmosphere and plasma links. Utilizing the optical transmission matrix, alongside the second moment theory and Wigner distribution functions, we derived analytical expressions for both the intensity distribution and propagation factors of the partially coherent flat-topped beam rectangular arrays affected by the atmospheric turbulence and plasma disturbances. The numerical results indicate that appropriately selecting parameters such as beam order, transverse spatial coherence width, and beam width can effectively mitigate the adverse effects on propagation properties caused by the turbulent atmosphere and plasma. Our results have significant implications for FSO communications within specific environmental contexts.